Act! 2005 for Dummies - Fredricks, Karen S. (Wiley Publishing, 2011)
ACT! 2005 will help you manage your business contacts and relationships (not just with customers, but also with prospects, vendors, and suppliers) more efficiently and effectively. But there is a catch—you have to ACTivate it. ACT! 2005 for Dummies helps you get your ACT together with basic information about fields, records, files, and navigation, and step-by-step guidelines for: